Maternal depression and anxiety associated with dental fear in children: a cohort of adolescent mothers in Southern Brazil - Vanessa Polina Pereira COSTA; Marcos Britto CORREA; Marília Leão GOETTEMS; Ricardo Tavares PINHEIRO; Flávio Fernando DEMARCO (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract Exposure to maternal symptoms of depression/anxiety has long-term negative consequences for child development, regardless of the contextual risk. The objective of this study was to investigate the relationship of the symptomatology of persistent maternal depression and anxiety with child dental fear. This study was nested in a cohort of adolescent mothers in southern Brazil. Symptomatology of maternal depression and anxiety was assessed during pregnancy and postpartum, when the mothers' children were 24-36 months old, using Beck Depression Inventory and Beck Anxiety Inventory. The mothers answered a questionnaire to assess dental fear in their children, and to obtain socioeconomic and demographic data. Both mothers and their children were submitted to clinical oral examination (n= 540 dyads) to obtain oral health data. Multivariate hierarchical Poisson regression analysis was used to determine associations (p < 0.05). At data collection, the prevalence of maternal depressive symptoms was 39.1%, and anxiety was observed in 27.8% of the mothers, whereas 21.6% of the children presented dental fear. In the adjusted analysis, children's dental fear was positively associated with mothers' presenting depressive symptomatology and caries experience. The depression symptomatology trajectory was not associated with dental fear, whereas mothers with persistent symptoms of anxiety reported higher prevalence of dental fear toward their offspring. The findings of symptomatology of maternal depression observed at data collection and persistence of anxiety may negatively impact the child's perception of dental fear. Mothers are the main caregivers and primary models responsible for transmitting health-related behaviors; consequently, mental disorders affecting mothers may negatively impact their children.